ANALYSIS OF REASONS AND AMOUNT OF CONSTRUCTION AND DEMOLITION WASTES: THE CASE OF ISTANBUL (TURKEY) - Erdinc, Oguzhan; Yetilmezsoy, Kaan (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2017)
Global increases in urbanization and industrialization have brought about a rapid development in the construction sector, worldwide. Solid waste accumulates during the construction, demolition, restoration, and the repairment phases of buildings. The control and management of solid waste is one of the modern world's leading problems. Construction and demolition is responsible for the majority of solid waste. This study details the quantities of waste realized and the associated reasons during the construction and demolition phases for the buildings of fourteen different projects of different sizes, serving different purposes. Some of the buildings are newly constructed, while and the rest were constructed following with firstly the demolition of an old building. To access the real sector data, a data pool has been provided by establishing contacts with sector companies of different sizes. In this regard, it enables a closer determination of the real field data of construction and demolition waste amounts.
Keywords: Construction Waste; Demolition Waste; Field Study; Questionnaire; Istanbul; ENVIRONMENTAL IMPACTS; DEBRIS; MODEL; MANAGEMENT; HEALTH; CHINA; SITE; Environmental Sciences & Ecology